2021
DOI: 10.3390/app11093736
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest UV-B and Photoperiod with Blue + Red LEDs as Strategies to Stimulate Carotenogenesis in Bell Peppers

Abstract: Background: Our objective was to evaluate carotenoid accumulation in bell peppers during shelf life under different light conditions. Methods: Fruit stored for 6 d at 7 °C received a 9 kJ m−2 UV-B treatment, while non-UV-treated were used as control (CTRL). Subsequently, all peppers were disposed for a retail sale period of 4 d at 20 °C with a photoperiod of 14 h under fluorescent light (FL) + 10 h under darkness (D), FL, or blue + red LEDs (BR LED). Results: Total antioxidant capacity (TAC) was increased by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
(52 reference statements)
1
15
0
Order By: Relevance
“…Angus) fruits, exposed to UV-B radiation (8.94 W m −2 , 19 min and 30 sec) 6 days after the harvest, and then kept under different light conditions for up to 4 days to simulate a retail sale period. The carotenoid profile highlighted that such a positive effect was particularly evident when UV-B treatment was followed by storage under fluorescent/blue-red LED day/night photoperiod [220].…”
Section: Terpenoids and Chlorophyllsmentioning
confidence: 99%
“…Angus) fruits, exposed to UV-B radiation (8.94 W m −2 , 19 min and 30 sec) 6 days after the harvest, and then kept under different light conditions for up to 4 days to simulate a retail sale period. The carotenoid profile highlighted that such a positive effect was particularly evident when UV-B treatment was followed by storage under fluorescent/blue-red LED day/night photoperiod [220].…”
Section: Terpenoids and Chlorophyllsmentioning
confidence: 99%
“…In fact, the wounding of fresh carrot has been demonstrated to be effective also in combination with UV-A, UV-B, and UV-C lighting, whose application has been related to the production of ROS and, consequently, to the production of antioxidant compounds to fight against such oxidative processes [18,19]. In this sense, a direct correlation has been found between the UV-B application and the biosynthesis of nutraceuticals, which was recently corroborated in red prickly pears [20], broccoli by-products [21], carrots [22], and red bell peppers [8,23] to enhance the accumulation of glucosinolates and sulforaphane, phenolics, and carotenoids, respectively. These studies showed that the external stress provoked by UV increases the transcription of genes (FMO GS-OX5 -flavin-monooxygenase glucosinolate S-oxygenase 5-and MYB51) involved in the biosynthetic pathway of glucosinolates [2], as well as the genetic code in charge of the secondary metabolism to counteract the ROS action when UV RESISTANCE LOCUS 8 (UVR8) is activated [24].…”
Section: Elicitor's Classification: Biotic and Abioticmentioning
confidence: 81%
“…In this sense, UVR8, as main UV-B receptors, are in charge to activate several transcription factors, such as COP1 (linked to HY5), as main stimulator of the PHYTOENE SYNTHASE (PSY), the first enzyme of carotenogenesis [13,57,58]. This behaviour has been recently shown in red peppers after a UV-B dose of 6 kJ m −2 applied before a short retailing period, which increased by 20 % the carotenoid accumulation, especially in combination with a blue + red LED photoperiod during the nights at supermarkets [59].…”
Section: Uv-b Treatment Enhanced the Biosynthesis Of Nutraceuticalsmentioning
confidence: 92%